Philippines-China relations, 2001–2008 dovetailing national interests. - De Guzman, Charles Joseph (2014)
This study shows that the Joint Marine Seismic Undertaking (JMSU) between China and the Philippines is an attempt of both countries to advance their respective national interests. Arguing that the foreign policies of China and the Philippines dovetailed during the administration of President Gloria Macapagal-Arroyo, the study situates the JMSU as (1) part of China’s overall foreign policy in Southeast Asia and (2) as an attempt to maintain good relations with the Philippines and help resolve tensions related to the South China
Sea disputes between the Philippines and China. The paper also shows that (3) the JMSU,
along with Chinese OD A, dovetailed with the Philippine government’s plan to promote economic development and facilitate energy security. Citing significant documents compiled by government agencies, newspaper and online articles, government officials’ speeches, and academic journals, the study shows how the Chinese of ficial development assistance (ODA) coincided and ran parallel to the signing of the Joint Maritime Seismic Undertaking. In
conclusion, the study suggests a direct, causal link, not just conjunction, among Chinese
ODA, the advancement of Beijing’s security interests, and the signing of the JMSU.
Keywords: Philippines -- Foreign relations -- China